Pengaruh Model Pembelajaran Problem-Solving Terhadap Kemampuan Berpikir Kreatif Siswa Pada Materi Pola Bilangan - Suna, Ramla; Mohidin, Abdul Djabar; Katili, Nancy; Abdullah, Abdul Wahab; Majid, Majid (Research in the Mathematical and Natural Sciences, 2022)
This study aims to determine the effect of using the Problem-Solving learning model on students' Creative Thinking Ability with Number Patterns. This study involved 40 students as the research sample consisted of two classes, every 20 students in class A and 20 students in class B. The research method used was Experimental research with Pretest-Posttest Control Group Design. The data collection technique was obtained through the pre-test and post-test results, and the data analysis technique used the covariance analysis test. The analysis results show that the creative thinking ability of students who are taught using the Problem-Solving model is better than the creative thinking skills of students trained using the direct learning model.